A Comparative Study of Green Banking Implementation between Indonesia Banks and Singapore Banks - Kezia Pratnya Theresa; Dwi Nita Aryani (PT. Anagata Sembagi Education, 2025)
The deterioration of the natural environment has become a significant global issue, Green Banking is a program where financial institutions prioritize environmental concerns within their operations and business activities. This research aims to examine and compare the progress of Indonesian banks and Singaporean banks in implementing green banking. This research employed ROE annual report, digital banking record, and green projects that banks participated in from 2019 to 2023. The analysis revealed that Indonesia and Singapore experienced a loss in 2019, but subsequently recovered their equity footing in 2020 and continued to do so through 2023. A statement from the banks' annual report indicated that digital banking played a role in maintaining banks' equity throughout the year, demonstrating the successful implementation of digital banking in both Indonesia and Singapore. A While Indonesia's green investment and loans prioritize supporting small green businesses, Singapore's approach is to assist larger enterprises that aim to adopt environmentally friendly practices. This research has revealed that both Indonesia and Singapore have successfully implemented green banking, and each country has developed its own approach to this implementation.